The understanding of Islamic Moderation (wasatiyyah al-Islam) and the hadiths on inter-religious relations in the Javanese pesantrens - Muhammad Irfan helmy; Ahmad Darojat Jumadil Kubro; Muhamad Ali (IAIN Salatiga, 2021)
The Wasatiyyah of Islam has been described as the value of moderation in Islam, emphasizing justice, balance, and tolerance. The Quran and al-Hadith contain these values, but they are often misunderstood and misapplied. The pesantren or Islamic boarding school, is an educational institution close to the community and it plays a key role in instilling the moderate values of Islam. This article aims at discussing the moderation of Islam in relation to other religions and religious communities as taught through the hadith and as understood among the teachers and students of three pesantrens in central Java. It investigates the teachers’ and students’ views of Islam as a religion among other religions, and their attitudes as the pesantren community toward other religious believers. It combines textual research employing a mukhtalif al-hadiṡ approach and living or lived hadith research. It argues that the hadiths on inter-religious relationship are understood as a necessity to be just towards faith, which means that one should believe that his own faith is correct but should keep tolerant towards other faiths. This means giving others the right to choose and implement their own faiths, behaving in a balanced way, and conducting healthy competition in various fields, especially the proselytization or dawah. With this textual understanding, the students have generally been quite well informed about the values of Islamic moderation and they seek to apply it in their religious and social life. The students have learned about the hadiths on interreligious relations and the moderate values primarily from their teachers although they have read directly from books and sometimes from social media. Wasatiyyah Islam digambarkan sebagai nilai moderasi dalam Islam, menekankan keadilan, keseimbangan, dan toleransi. Al-Qur'an dan al-Hadis mengandung nilai-nilai ini, tetapi sering disalahpahami dan diterapkan secara salah. Pesantren merupakan lembaga pendidikan yang dekat dengan masyarakat dan berperan penting dalam menanamkan nilai-nilai moderat Islam. Artikel ini bertujuan membahas moderasi Islam dalam kaitannya dengan agama dan umat beragama lain sebagaimana diajarkan melalui hadis dan sebagaimana dipahami para guru dan santri di tiga pesantren di Jawa Tengah. Artikel ini menyelidiki pandangan siswa tentang Islam sebagai agama di antara agama-agama lain, dan sikap mereka sebagai komunitas pesantren terhadap pemeluk agama lain. Ini menggabungkan penelitian tekstual yang menggunakan pendekatan mukhtalif al-hadiṡ dan penelitian hadits hidup (living or lived hadith). Artikel ini berargumen bahwa hadis-hadis tentang hubungan antarumat beragama dipahami sebagai keharusan untuk bersikap adil terhadap keimanan, yang berarti bahwa seseorang harus percaya bahwa imannya sendiri benar tetapi harus tetap toleran terhadap agama lain. Ini artinya memberikan hak kepada orang lain untuk memilih dan menjalankan keyakinannya sendiri, berperilaku seimbang, dan melakukan persaingan yang sehat di berbagai bidang, terutama dakwah. Dengan pemahaman tekstual ini, para santri secara umum telah terinformasi dengan baik tentang nilai-nilai moderasi Islam dan mereka terus menerapkannya dalam kehidupan keagamaan dan sosial mereka. Para siswa telah belajar tentang hadits tentang hubungan antaragama dan nilai-nilai moderat terutama dari guru mereka meskipun mereka telah membaca langsung dari buku dan kadang-kadang dari media sosial.